2005
DOI: 10.1002/jctb.1308
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical wet scrubbers and biofiltration for control of volatile organic compounds using GC/MS techniques and kinetic analysis

Abstract: Increasing public concerns and EPA air regulations in non-attainment zones necessitate the remediation of volatile organic compounds (VOCs) generated in the poultry-rendering industry. Wet scrubbers using chlorine dioxide (ClO 2 ) have low overall removal efficiencies due to lack of reactivity with aldehydes. Contrary to wet scrubbers, a biofilter system successfully treated the aldehyde fraction, based on GC/MS analysis of inlet and outlet streams. Total VOC removal efficiencies ranged from 40 to 100% for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Deionized water was produced by a Millipore ™ Milli-Q water purification system (Merck Millipore, Darmstadt, Germany). 6 For the preparation of ZnWO4 microspheres, 10 mmol of zinc nitrate (Zn(NO3)2) and 10 mmol of tungstic acid were first dissolved in 10 mL of deionized water and 10 mL of concentrated ammonia solution, respectively. Subsequently, the tungstic acid/ammonia solution was added into the Zn (NO3) 2 aqueous solution and stirred for about half an hour.…”
Section: Synthesis Of Hierarchical Porous Znwomentioning
confidence: 99%
See 1 more Smart Citation
“…Deionized water was produced by a Millipore ™ Milli-Q water purification system (Merck Millipore, Darmstadt, Germany). 6 For the preparation of ZnWO4 microspheres, 10 mmol of zinc nitrate (Zn(NO3)2) and 10 mmol of tungstic acid were first dissolved in 10 mL of deionized water and 10 mL of concentrated ammonia solution, respectively. Subsequently, the tungstic acid/ammonia solution was added into the Zn (NO3) 2 aqueous solution and stirred for about half an hour.…”
Section: Synthesis Of Hierarchical Porous Znwomentioning
confidence: 99%
“…Therefore, it is essential to control and reduce NOx concentrations to mitigate the air pollution problems in China. Various techniques have been developed for NOx abatement, including selective catalytic and non-catalytic reduction [2,3], three-way catalysis [4], wet scrubbing and biofiltration [5,6], and adsorption [7]. However, most of these approaches have been hindered in application because they either need high temperature to initiate the catalytic conversion reactions or cause secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal bed moisture content in biofiltration ranges from 40% to 70% (on a weight basis), although optimal microbial activities have been recorded at lower moisture contents for xerophilic microbial communities [9,72,73]. Excessive moisture may cause a rapid organic packing media structural deterioration, the development of anaerobic zones and limit gas pollutant mass transfer from the gas phase to the biofilm in the particular case of hydrophobic gas pollutants [8,46,74]. On the other hand, a low packing humidity entails detrimental effects on microbial activity and affect packed bed structure by promoting the formation of preferential pathways as above mentioned [7].…”
Section: Packing Materialsmentioning
confidence: 98%
“…The operating conditions are reported in Table 2. It should be observed that the considered pollutant concentrations were selected according to the range of values reported in the literature [2,[30][31][32].…”
Section: Operating Conditions and Start-upmentioning
confidence: 99%